2007
DOI: 10.1111/j.1462-2920.2007.01371.x
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia‐oxidizing bacterial community composition in estuarine and oceanic environments assessed using a functional gene microarray

Abstract: The relationship between environmental factors and functional gene diversity of ammonia-oxidizing bacteria (AOB) was investigated across a transect from the freshwater portions of the Chesapeake Bay and Choptank River out into the Sargasso Sea. Oligonucleotide probes (70-bp) designed to represent the diversity of ammonia monooxygenase (amoA) genes from Chesapeake Bay clone libraries and cultivated AOB were used to construct a glass slide microarray. Hybridization patterns among the probes in 14 samples along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 40 publications
(75 reference statements)
5
75
0
1
Order By: Relevance
“…This observation confirms previous studies that find that the dominant AOB in estuarine and marine environments appear to fall within divergent evolutionary clades (McCaig et al, 1994;Freitag and Prosser, 2004;Ward et al, 2007;Mosier and Francis, 2008). So far, there are no cultured isolates from this group, although Mosier and Francis, (2008) found sequences in an enrichment culture from the San Francisco Bay estuary.…”
Section: Discussionsupporting
confidence: 77%
“…This observation confirms previous studies that find that the dominant AOB in estuarine and marine environments appear to fall within divergent evolutionary clades (McCaig et al, 1994;Freitag and Prosser, 2004;Ward et al, 2007;Mosier and Francis, 2008). So far, there are no cultured isolates from this group, although Mosier and Francis, (2008) found sequences in an enrichment culture from the San Francisco Bay estuary.…”
Section: Discussionsupporting
confidence: 77%
“…We used the RFR from the functional gene microarray (Ward et al, 2007;Bulow et al, 2008) to quantify the relative contribution of each archetype to the total nirS signal and determine the distribution of nirS-containing phylotypes in both the PIE and GSM marshes. The RFR for the 39 archetypes found in both marshes was remarkably consistent, with only minor differences as a result of fertilization in the GSM experiment, and no differences as a result of fertilization in the PIE experiment (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…After amplification, PCR products were pooled and purified with the QIAquick PCR purification kit (Qiagen). PCR products were then labeled using the Klenow enzyme and hybridized to the array following standard methods (Ward et al, 2007;Bulow et al, 2008). After hybridization, the slides were washed (Ward et al, 2007) and scanned on an Agilent Laser Scanner (Agilent Technologies, Palo Alto, CA, USA).…”
Section: Microarray Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular approaches, such as functional gene arrays, facilitate a relatively easy assessment of the information in the microbenthic community, including community structure and function (Lu et al, 2012). Various studies have demonstrated the capacity of functional gene arrays to detect microbial community responses to environmental stressors Liu et al, 2010;Wang et al, 2009;Ward et al, 2007;Wu et al, 2008;Yergeau et al, 2007;Zhou, 2003), including heavily contaminated habitats (Lu et al, 2012;Neufeld et al, 2006;Van Nostrand et al, 2009;Xie et al, 2011). The results of these studies and other approaches evaluating the response of bacterial communities on environmental perturbation (chemically or physically) have demonstrated changes in the respective community structure and function (dos Santos et al, 2011;Findlay et al, 1990;Suarez-Suarez et al, 2011), thereby forming the basis for our hypothesis.…”
Section: Introductionmentioning
confidence: 99%